Between Theory and Practice: The Configuration of the Pedagogical Experience by Students of the Faculty of Basic Sciences, Engineering and Architecture of the University Corporation of the Caribbean (CECAR) - Acosta, Bessy Karina Flórez; Támara, Víctor Enrique Rivera; Molina, Héctor Fabio Parra; Vásquez, Yenny Andrea Belalcázar; Torres, Daniel Enrique Carranza (Journal of Cultural Analysis and Social Change, 2025)
The present study explores how students of the faculty of Basic Sciences, Engineering and Architecture of the University Corporation of the Caribbean (CECAR) They configure their pedagogical experience within the framework of the Institutional Pedagogical Model and the Institutional Educational Project (PEI, 2022). A qualitative interpretative design was used, using focus groups with 12 students from the Faculty of Basic Sciences, Engineering and Architecture (3rd-8th semester). The sessions, recorded and transcribed, were analyzed with MAXQDA software by open and axial coding, based on Dubet’s Sociology of Experience (2010), complemented by Tinto (1993), Foucault (1994) and Coleman (1988). The findings reveal a strong but partial academic social integration, reflexive subjectivation that negotiates identities in tension, and resilient strategies supported by social capital, Evidence of mismatches between the design of the PEI and student practice. It is concluded that the pedagogical experience in CECAR transcends the institutional model through the student agency, suggesting the need to review resources, methodologies and student participation to align design and reality.